Selling and negotiation skills : a pragmatic approach - Chaudhary, Prashant Vilas (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"This book is a complete guide to learning the critical selling and negotiation skills to gain a competitive edge in a challenging business environment. The volume covers various negotiation approaches, strategies, tactics and styles that are adaptable and compatible with emerging business models and technologies. Businesses worldwide are adapting to changing consumer behaviour and focusing on more sustainable and future-ready selling and negotiation strategies. Richly illustrated with examples from diverse domains and real-life situations for an easy understanding of the subject, this book looks at strategies, tactics, and styles for negotiation and the tools or technologies used for effectively selling; business cases and scenarios that illustrate the direct application of concepts, making the book practical, accessible, relevant and customer-centric selling and negotiation strategies, processes and approaches. A valuable companion for students, teachers, research scholars and professionals working in sales, business and management, this revised edition will also be of interest to those working in the areas of global business and trade, international affairs, marketing, and economics"--
Selling: fundamentals and modern practices -- Selling process: journey towards closing the deal -- Fundamental concepts, types and conceptual instruments of negotiation -- Styles, strategies and tactics of negotiation -- Negotiation process -- journey towards agreement, consensus and collaboration -- Dealing with 'difficult' people and situations.
Keywords: Selling; Negotiation in business; BUSINESS & ECONOMICS / Sales & Selling; BUSINESS & ECONOMICS / Industries / Service Industries